Adolescent Violence Towards Parents – The Known and Unknowns. Issue 4 (December 2016) - Moulds, Lauren; Day, Andrew; Mildred, Helen; Miller, Peter; Casey, Sharon
Abstract : Adolescent violence towards parents is one of the most poorly understood forms of family violence despite it being relatively common. This paper presents an overview of current knowledge about adolescent violence towards parents for practitioners who work with families, considering issues around definition, prevalence, impacts, and the key characteristics of perpetrators. It is concluded that both clinical and justice responses are, at present, not well informed by basic knowledge of the circumstances in which adolescent violence towards parents occurs, and there is a need to work systematically with families to balance safety and welfare needs.